The indomitable Francis H. Cook of Spokane : a man of vision - Woodward, Doris J. (Pacific northwesterner, 2010)
"Francis H. Cook was one of Spokane, Washington's founding fathers, as well as the "Father of Mount Spokane State Park." Starting Spokane's first newspaper, building its first motorized streetcar line, developing the nucleus of what became Spokane's renowned Manito Park, and building the first road to the top of Mt. Spokane were among Cook's many accomplishments. Not only a printer, editor and publisher, he was also a Washington Territorial Legislature president, a builder, developer, inventor, surveyor, farmer and Spokane's greatest promoter in its early days."--Publisher description.